Allergen-specific immunotherapy: which outcome measures are useful in monitoring clinical trials? - Pfaar, Oliver; Kleine-Tebbe, Jörg; Hörmann, Karl; Klimek, Ludger (Immunology and allergy clinics of North America, 2011)
Various clinical outcome measures are commonly applied in clinical trials on specific immunotherapy for allergic rhinoconjunctivitis with or without asthma to provide evidence of its clinical efficacy. These "primary endpoints" measure clinical symptoms as well as the use for concomitant medication. "Secondary outcome endpoints" are represented by health-related quality of life (HRQoL), "well-days," provocation-tests, in vitro tests and others. This article reviews different methods assessing the clinical outcome of trials on both subcutaneous and sublingual immunotherapy, and highlights potential advantages and drawbacks of each method.